Composite membrane material containing bridging layer as well as preparation method and application of composite membrane material

By using composite film materials containing a bridge layer in the membrane technology, using the combination of 3D printing and zirconium-based organic frame materials, the problems of low oil-water separation efficiency and poor recycling stability in the existing membrane technology are solved, and efficient oil-water separation and stable recycling of the membrane are achieved.

CN119869244AInactive Publication Date: 2025-04-25ZHEJIANG NORMAL UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510356173.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing membrane technology has problems such as membrane pollution, low separation efficiency and poor recycling stability during oil-water separation.

Method used

A composite film material containing a bridge layer consisting of a base film (such as acrylonitrile-butadiene-styrene copolymer or polylactic acid), a bridge layer (including polymers derived from phenol monomers), and a zirconium-based organic frame material. The base film is prepared by 3D printing, and a bridge layer is formed on its surface to improve surface roughness and hydrophilicity. Then, the zirconium-based organic frame material is applied to the side on the bridge layer facing away from the base film to form a composite separation membrane.

Benefits of technology

Good water flux, oil-water separation efficiency and membrane recycling stability are achieved, and the problems of membrane pollution and low separation efficiency are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869244A_ABST
    Figure CN119869244A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of separation membranes, and particularly relates to a composite membrane material containing a bridging layer and a preparation method and application of the composite membrane material. The composite membrane material comprises: a base membrane comprising any one of an acrylonitrile-butadiene-styrene copolymer or polylactic acid; the bridging layer is positioned on one side surface of the base film and comprises a polymer, and the polymer comprises a structural unit derived from a phenol monomer; the composite film further comprises a zirconium-based organic framework material, and the zirconium-based organic framework material is located on the surface of the side, away from the base film, of the bridging layer. The composite membrane material provided by the invention can ensure the cyclic utilization stability of the membrane on the basis of good oil-water separation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of separation membranes, and in particular to a composite membrane material comprising a bridging layer, and a preparation method and application thereof. Background Art

[0002] Membrane technology has become the most widely used technology for oil-water separation due to its advantages such as high separation efficiency, low cost and no secondary pollution. However, membrane fouling and membrane separation efficiency are still huge challenges restricting the application of membranes. Summary of the invention

[0003] In view of the above problems, the present application provides a composite membrane material including a bridging layer and a preparation method and application thereof. The composite membrane material has good oil-water separation efficiency and can also ensure the stability of the recycling of the membrane itself.

[0004] In one aspect, the present application provides a composite membrane material comprising a bridging layer, the composite membrane material comprising: Base film: including any one of acrylonitrile-butadiene-styrene copolymer or polylactic acid; A bridging layer is located on one side of the base film; the bridging layer includes a polymer, and the polymer includes a structural unit derived from a phenol monomer; Zirconium-based organic framework material: located on a surface of the bridging layer facing away from the base film.

[0005] In some embodiments, the phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols; and / or; The weight average molecular weight of the above polymer is 1000-30000.

[0006] In some embodiments, the zirconium-based organic framework material comprises any one or more of micropores, mesopores, or macropores, and at least one of the micropores, mesopores, or macropores is interconnected to form a porous structure; and / or; The zirconium-based organic framework material includes particles, and the average particle size Dv50 of the particles is 50nm~300nm; and / or; The zirconium-based organic framework material comprises particles, and the specific surface area of ​​the particles is 1000 m 2 / g ~1500 m 2 / g.

[0007] In some embodiments, the base film is made by 3D printing; The base film has a porous structure, and the average pore size of the porous structure is 100 μm to 400 μm; The average pore height of the porous structure is 100 μm to 500 μm.

[0008] In some embodiments, the thickness of the bridging layer is 4% to 20% of the thickness of the base film.

[0009] The second aspect of the present application is to provide a method for preparing the composite film according to the first aspect, the preparation method comprising the following preparation process: Providing a base film: the base film is prepared by a melt deposition method in 3D printing; placing the base film in a solution containing a phenol-derived monomer and shaking the solution to form a bridging layer; A zirconium-based organic framework material is coated on a surface of the bridge layer that is away from the base membrane to form a composite separation membrane.

[0010] In some embodiments, the shaking treatment is performed at room temperature, the shaking frequency is controlled to be 20 rpm to 300 rpm, and the shaking treatment time is 10 h to 30 h.

[0011] In some embodiments, the step of preparing the zirconium-based organic framework material comprises: dispersing the zirconium-based organic framework material in deionized water to form a suspension, wherein the concentration of the suspension is greater than zero and less than 20 g / mL.

[0012] In some embodiments, the zirconium-based organic framework material is dispersed in deionized water to form a suspension, and the concentration of the suspension is 8 g / mL to 16 g / mL.

[0013] In some embodiments, the zirconium-based organic framework material particles are formed by: Add L-aspartic acid to a reaction container filled with deionized water, stir at room temperature for a period of time, add a zirconium ion precursor in batches, stir evenly to obtain a mixed solution, heat the mixed solution for a period of time, cool to room temperature after the reaction is completed to obtain a suspension, and centrifuge the suspension to obtain the zirconium-based organic framework material.

[0014] The third aspect of the present application is to provide an application of a composite membrane material comprising a bridging layer in the field of oil-water separation. The composite membrane material is the composite membrane material described in the first aspect or a composite membrane material prepared by the preparation method described in the second aspect.

[0015] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below.

[0016] Beneficial technical effects of this application: (1) The composite membrane material provided in this application has good water flux.

[0017] (2) The composite membrane material provided in this application has good oil-water separation efficiency.

[0018] (3) The composite membrane material provided in this application has good cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings: Figure 1A and Figure 1B The following is a process flow chart of preparing the composite membrane according to the embodiment of the present application; Figure 2 A scanning electron microscope image (SEM) of a zirconium-based organic framework material according to an embodiment of the present application; Figure 3A , Figure 3C , Figure 3D and Figure 3E A scanning electron microscope image (SEM) of a composite membrane illustrated in an embodiment of the present application; Figure 3B Energy dispersive X-ray spectrometer (EDS) diagram of the composite film shown in the embodiment of the present application Figure 3F A scanning electron microscope image (SEM) of a composite membrane illustrated as a comparative example of the present application; Figure 4A This is a test diagram of the water contact angle of the composite membrane illustrated in the embodiment of the present application; Figure 4B A bar graph showing the water contact angle of the composite membrane according to an embodiment of the present application; Figure 5A This is a test diagram of the underwater oil contact angle of the composite membrane illustrated in the embodiment of the present application; Figure 5B A bar graph showing the underwater oil contact angle of a composite membrane according to an embodiment of the present application; Figure 6 A bar graph showing the water flux of a composite membrane according to an embodiment of the present application; Figure 7 A bar graph showing the separation effect of the composite membrane on different oil types according to the embodiment of the present application; Figure 8 This is a test diagram of the cyclic stability of the composite membrane after multiple uses according to an embodiment of the present application. DETAILED DESCRIPTION

[0020] Hereinafter, the composite membrane material including a bridging layer, its preparation method and application embodiments of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0021] In recent years, due to the increasing demand for oil caused by the development of industrial production, oily pollutants in industrial wastewater have attracted widespread attention. So far, different technical solutions have been developed for oil-water separation and the recovery and utilization of leaked crude oil, such as gravity sedimentation, combustion, biodegradation and chemical coagulation. However, these methods generally have disadvantages such as high cost, low efficiency, and difficult operation, and may even cause secondary pollution. For example, the combustion method will produce carcinogenic gases and pollute the atmosphere. Therefore, it is urgent to develop efficient and simple methods to treat oil pollution.

[0022] Membrane separation is a popular technology widely used in the field of water treatment. Compared with other treatment methods, it has the advantages of simple operation, low energy consumption and high separation efficiency. It is considered to be one of the most competitive technologies used in the field of oil-water separation. However, membrane fouling problems and the trade-off effect between permeability and selectivity have always limited the application of membrane separation technology. At the same time, the limited chemical stability of the membrane under adverse conditions also affects the service life of the membrane. In addition, the exploration and implementation of innovative membrane technologies, such as 3D printed membranes, stimuli-responsive membranes and biomimetic membranes, have become the forefront of research. These advances mark the transformative potential for improving the scope and enhancing the application of membrane-based separation processes.

[0023] 3D printing technology can accurately design and control the macroscopic structure of the membrane through computers, such as cutting the membrane pore size, porosity and surface morphology with unparalleled precision, and also has the advantage of being able to achieve one-time membrane formation. 3D printing technology is mainly divided into four categories: photopolymerization, powder fusion, material extrusion and sheet lamination. Among them, fused deposition manufacturing (FDM) is widely used because of its low cost, simple operation and high speed. FDM technology extrude thermoplastic plastic filaments on a tray according to the coordinates preset by the software, and a membrane structure is formed after two layers of plastic filaments are stacked.

[0024] As a model material for 3D printing technology, acrylonitrile butadiene styrene (ABS) has the common properties of the three components and is a non-toxic material with good impact resistance, heat resistance, low temperature resistance, etc. For example, polylactic acid (PLA) has the advantages of low melting point, not easy to warp, good interlayer adhesion, etc., and is also convenient for printing.

[0025] Therefore, compared with traditional commercial membranes, 3D printed membranes are not only tougher and more resistant to acid and alkali, but also have significantly reduced toxicity. 3D printed membranes bring new possibilities for the optimization of materials and structures of commercial membranes. However, 3D printed membranes cannot be used directly as separation membranes. For example, the hydrophobic characteristics of 3D printed ABS membranes cause serious membrane contamination during oil-water separation, while 3D printed PLA membranes have unsatisfactory surface wettability, so further modification or composite treatment is required.

[0026] Therefore, the present application provides a composite membrane material comprising a bridging layer, the composite membrane material comprising: a base membrane, the base membrane comprising any one of acrylonitrile-butadiene-styrene copolymer or polylactic acid; a bridging layer located on one side surface of the above-mentioned base membrane, the bridging layer comprising a polymer, the polymer comprising a structural unit derived from a phenol-based monomer; the composite membrane also comprises zirconium-based organic framework material particles, the zirconium-based organic framework material is located on one side surface of the above-mentioned bridging layer away from the above-mentioned base membrane.

[0027] The base membrane of the present application is used as a support membrane, and the bridging layer is connected to the base membrane on one side and to the zirconium-based organic framework material on the other side. This is because the base membrane itself has low roughness and strong hydrophobicity, and it is not easy to form zirconium-based organic framework material particles on its surface. The present application forms a bridging layer on the surface of the base membrane, which improves the surface roughness of the membrane and facilitates the attachment of the zirconium-based organic framework material. At the same time, since the monomers forming the bridging layer contain hydrophilic functional groups, such as hydroxyl groups or phenolic hydroxyl groups, it is beneficial to further improve the hydrophilicity of the membrane. In addition, the high specific surface area of ​​the zirconium-based organic framework material improves the oil-water separation efficiency and the cyclic stability of the membrane itself.

[0028] The composite membrane material provided in the present application has certain application prospects in the field of oil-water separation. For example, in the field of oily wastewater, the composite membrane material provided in the present application is further made into the required composite membrane assembly, and the composite membrane assembly is placed in an industrial membrane oily wastewater treatment device for treating oily wastewater.

[0029] The first aspect of the present application is to provide a composite membrane material comprising a bridging layer, the composite membrane material comprising: a base membrane, the base membrane comprising any one of acrylonitrile-butadiene-styrene copolymer or polylactic acid; a bridging layer located on one side surface of the base membrane, the bridging layer comprising a polymer, the polymer comprising a structural unit derived from a phenolic monomer; the composite membrane also comprises zirconium-based organic framework material particles, the zirconium-based organic framework material is located on one side surface of the bridging layer away from the base membrane.

[0030] The base film of the present application is mainly used as a support film. When the material of the support film includes acrylonitrile-butadiene-styrene copolymer, the acrylonitrile-butadiene-styrene copolymer contains structural units derived from acrylonitrile monomers, structural units derived from butadiene monomers, and structural units derived from styrene copolymers; based on the total molar number of each monomer, the molar percentage content of the structural unit derived from the acrylonitrile monomer is 15%~35%, the molar percentage content of the structural unit derived from the butadiene monomer is 5%~30%, and the molar percentage content of the structural unit derived from the styrene copolymer is 40%~60%.

[0031] When the material of the support film includes polylactic acid, the weight average molecular weight of the polylactic acid is 60,000 to 600,000, and the molar content of the L optical isomer in the polylactic acid is 85% to 99%.

[0032] The base film of the present application is prepared by a 3D printing method, which will be described in detail in the following embodiments.

[0033] The polymer of the present application refers to a collection of macromolecules that are chemically uniform but different in degree of polymerization, molar mass and chain length prepared by polymerization. The term also includes derivatives of such macromolecular collections formed by polymerization, i.e. compounds that can be obtained by reaction of functional groups in the above macromolecules, such as addition or substitution, and can be chemically uniform or chemically inhomogeneous.

[0034] The copolymer in this application refers to a polymer formed by polymerization of two or more different monomers (monomers are the basic units that make up a polymer). Unlike homopolymers (polymerized from a single type of monomer), copolymers contain different types of repeating units (monomers) in their molecular chains.

[0035] The bridging layer of the present application plays a bridging role. This is because the base film itself has low roughness and strong hydrophobicity, and it is not easy to form a zirconium-based organic framework material on its surface. The present application forms a bridging layer on the surface of the base film, which improves the surface roughness of the film and facilitates the attachment of the zirconium-based organic framework material. At the same time, since the monomers forming the bridging layer contain hydrophilic functional groups, such as hydroxyl groups or phenolic hydroxyl groups, it is beneficial to further improve the hydrophilicity of the film.

[0036] The zirconium-based organic framework material (Zr-MOFs) of the present application is a type of porous crystalline material formed by zirconium metal nodes and organic ligands connected by coordination bonds. The material has a very high specific surface area and an adjustable pore structure, and the material itself has high thermal and chemical stability. Therefore, the zirconium-based organic framework material of the present application is conducive to improving the oil-water separation efficiency and the cycle stability of the membrane itself.

[0037] In some embodiments of the present application, the phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols.

[0038] The CAS number of dopamine in this application is 51-61-6, and the chemical formula is C8H 11 NO2, with a molecular weight of 153.18, actually exists in the form of its hydrochloride salt.

[0039] The CAS number of the tannic acid in this application is 1401-55-4, and the chemical formula is C 76 H 52 O 46 .

[0040] The CAS number of the tea polyphenols in this application is 84650-60-2, and the chemical formula is C 17 H 19 N3O.

[0041] The polymer material formed by the phenol monomers listed above in the present application has good adhesion, which is beneficial to improving the roughness of the base film surface. The polymer material is highly chemically stable and is also convenient for biodegradation.

[0042] In some embodiments of the present application, the weight average molecular weight of the above polymer is 1000-30000.

[0043] The weight average molecular weight of the present application refers to the sum of the products of the weight fractions of molecules of different molecular weights in the polymer and their corresponding molecular weights. The weight average molecular weight of the polymer of the present application can be tested by methods known in the art, such as gel chromatography, and the specific test standards can refer to the conventional standards in the art.

[0044] In these embodiments, the present application discloses that the weight average molecular weight of any one of polydopamine (PDA), tannic acid polymer, and tea polyphenol polymer is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, 13000, 14000, 15000, 16000, 17000, 18000, 19000, 20000, 21000, 22000, 23000, 24000, 25000, 26000, 27000, 28000, 29000, 30000 or any one of the values ​​satisfying any two of the above ranges.

[0045] In some embodiments of the present application, the zirconium-based organic framework material comprises any one or more of micropores, mesopores or macropores, and at least one of the micropores, mesopores or macropores is interconnected to form a porous structure.

[0046] In some embodiments of the present application, the zirconium-based organic framework material includes particles, and the average particle size Dv50 of the particles is 50nm~300nm; In some embodiments of the present application, the zirconium-based organic framework material includes particles, and the specific surface area of ​​the particles is 1000 m 2 / g ~1500 m 2 / g.

[0047] Dv50 in this application refers to the volume particle size distribution of particles, the volume of particles with a particle size larger than it accounts for 50%, and the volume of particles smaller than it also accounts for 50%, also known as the median diameter, which is usually used to represent the average particle size of particles. In these embodiments, this application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by calculation.

[0048] The present application discloses in these embodiments that the average particle size Dv50 of the particles of the zirconium-based organic framework material is 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm or any one of the range values ​​of any two of the above. The micropores of the present application refer to pore sizes less than 2nm, the mesopores refer to pore sizes between 2nm and 50nm, and the macropores refer to pore sizes greater than 50nm. The present application can perform scanning electron microscopy (SEM) or transmission electron microscopy (TEM) on the zirconium-based organic framework material to obtain the pore structure and pore size of the zirconium-based organic framework material.

[0049] The specific surface area BET in this application refers to the total surface area of ​​the porous material surface, usually in square meters per gram (m² / g). It reflects the complexity of the material surface and the characteristics of the pore structure. It is usually measured and calculated by the Brunauer-Emmett-Teller theory. For example, referring to GB / T 19587-2004, the nitrogen adsorption specific surface area analysis test method is used for testing, and the specific surface area of ​​the porous material is calculated by the BET (Brunauer Emmett Teller) method. The test instrument can be the TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA.

[0050] The present application discloses in these examples that the specific surface area of ​​the particles is 1000 m 2 / g, 1100 m 2 / g, 1200 m 2 / g, 1300 m 2 / g, 1400 m 2 / g, 1500 m 2 / g or any of the values ​​satisfying any two of the above ranges.

[0051] In some embodiments of the present application, the base film is prepared by a 3D printing method. Specifically, any conventional 3D printing machine in the art is used for fused deposition modeling (FDM), and a base film bare film model is designed using 3Ds Max software, which provides accurate digital dimensions. The model is imported into a 3D printer, and thermoplastic filaments are extruded onto the printer bed by fused deposition, and then the base film bare film is obtained by post-processing.

[0052] The base membrane prepared by the 3D printing method in the present application has a porous structure, and the holes in the porous structure are arranged neatly and have regular shapes.

[0053] In some embodiments of the present application, the average pore size of the porous structure is 100 μm to 400 μm; the average pore height of the porous structure is 100 μm to 500 μm.

[0054] The average pore size in the present application includes the average pore width, and the average pore height refers to the average height of the porous structure, wherein the height direction is consistent with or parallel to the thickness direction of the membrane.

[0055] In some embodiments of the present application, the base film is also plasma treated to further increase the water flux of the base film, wherein the plasma treatment here includes any conventional method in the art, such as using air as the reaction gas, controlling the RF frequency of the plasma treatment equipment to 12MHz~15MHz, the RF power to 6.8W~18W, and the plasma treatment time to 2.5min~3.5min.

[0056] In some embodiments of the present application, the thickness of the bridging layer is 4% to 20% of the thickness of the base film.

[0057] The thickness direction of the bridging layer of the present application is consistent with the thickness direction of the base film.

[0058] The present application discloses in some embodiments that the thickness of the bridging layer is any one of 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, and 20% of the thickness of the base film or any one of the ranges of any two of the above.

[0059] The second aspect of the present application is to provide a method for preparing the composite membrane material according to the first aspect, the preparation method comprising the following preparation process: Figure 1A and Figure 1B Hint: S100, providing a base film: preparing the base film by a melt deposition method in 3D printing; S200, placing the base film in a solution containing a phenol-derived monomer, and oscillating the solution to form a bridging layer; S300, coating zirconium-based organic framework material particles on the surface of the bridging layer away from the base membrane to form a composite separation membrane material.

[0060] In some embodiments of the present application, the above-mentioned oscillation treatment is carried out at room temperature, the oscillation frequency is controlled to be 20 rpm~300 rpm, and the oscillation treatment time is 10h~30h.

[0061] The present application adopts the above preparation to form a bridging layer containing the above polymer on one surface of the base film.

[0062] In some embodiments of the present application, the preparation method of the polydopamine (PDA) bridging layer is as follows: Prepare a polydopamine (PDA) solution: In a beaker, dissolve Tris in an aqueous solution, adjust the pH to 8.5 with HCl, then add dopamine to the beaker and pre-stir with a glass rod. After the color turns brown, put a rotor in and stir on a stirrer until the color turns black and an oil film exists on the surface. The weight average molecular weight of the formed polydopamine is 1000~30000.

[0063] Preparation of a bridging layer: placing the ABS base film obtained in the above step in the above polydopamine (PDA) solution, oscillating it at room temperature for 24 hours, with an oscillation frequency of 20 rpm to 300 rpm and an oscillation treatment time of 10 hours to 30 hours, to obtain a bridging layer, wherein the thickness of the bridging layer is 4% to 20% of the thickness of the base film.

[0064] In some embodiments of the present application, the steps of preparing the zirconium-based organic framework material include: The zirconium-based organic framework material particles are dispersed in deionized water to form a suspension, and the concentration of the suspension is greater than zero and less than 20 g / mL.

[0065] The concentration of the suspension in the present application refers to the ratio between the mass of the zirconium-based organic framework material particles and the volume of deionized water.

[0066] In some embodiments of the present application, the concentration of the suspension is 8 g / mL to 16 g / mL.

[0067] The concentration of the suspension in this application affects the amount of zirconium-based organic framework material attached to the surface of one side of the bridge layer. Generally speaking, the appropriate amount of attachment will affect the performance of the composite membrane. The concentration of the suspension selected in this application is 8g / mL to 16g / mL to facilitate the good performance of the composite membrane.

[0068] The present application discloses in these embodiments that the concentration of the suspension is any one of 1 g / mL, 2 g / mL, 3 g / mL, 4 g / mL, 5 g / mL, 6 g / mL, 7 g / mL, 8 g / mL, 9 g / mL, 10 g / mL, 11 g / mL, 12 g / mL, 13 g / mL, 14 g / mL, 15 g / mL, 16 g / mL, 17 g / mL, 18 g / mL, and 19 g / mL, or any one of the values ​​satisfying any two ranges above.

[0069] In some embodiments of the present application, the steps of preparing the zirconium-based organic framework material particles include: L-aspartic acid is added to a reaction container containing deionized water, and the mixture is stirred at room temperature for a period of time. A precursor of zirconium ions is added in batches and stirred evenly to obtain a mixed solution. The mixed solution is heated to react for a period of time. After the reaction is completed, the mixture is cooled to room temperature to obtain a suspension. The suspension is centrifuged to obtain the zirconium-based organic framework material particles (numbered MIP-202(Zr)MOFs).

[0070] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0071] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0072] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents were purchased at AR grade, and all reactions were carried out under argon protection. Unless otherwise specified, all reagents were obtained from commercial channels.

[0073] Example 1-1 A method for preparing a composite membrane material comprising a bridging layer is provided, the method comprising: S100, providing base film: an industrial-grade 3D printer (F170, Stratasys, USA) uses the melt deposition technology to print out an ABS base film with uniform and regular membrane pores according to the designed coordinates. The thickness of the base film is 254 μm. The acrylonitrile-butadiene-styrene (ABS) copolymer used has a CAS number of 9003-56-9 and a molecular formula of C 15 H 17 N, molecular weight is 211.30218, the molar ratio of each monomer in acrylonitrile-butadiene-styrene copolymer is: acrylonitrile: butadiene: styrene = 1:1:2, and the accuracy of the 3D printer is set to 0.005 inches. Since the printed model needs to be melt-deposited on the soluble support material, it is immersed in a sodium hydroxide solution at a temperature of 60°C and a pH of 12 for 5 minutes until the model can be easily peeled off. The ABS base film with a pore size of 170μm×330μm is printed.

[0074] S210, preparing a solution containing a bridging layer polymer: in a 100 mL beaker, dissolving 1.211 g of Tris in 95 mL of aqueous solution, adjusting the pH to 8.5 with HCl, then adding 0.2 g of dopamine to the beaker, and pre-stirring with a glass rod, after the color turns brown, putting a rotor in the stirrer and stirring at a speed of 750 r / min, stirring for 12 h until the color turns black and an oil film exists on the surface, and the weight average molecular weight of the formed polydopamine is 13550; S220, preparing a bridging layer: placing the ABS base film prepared in step S100 in the solution of step S210, and oscillating the base film at room temperature for 24 hours with an oscillation frequency of 100 rpm to prepare a bridging layer, wherein the thickness of the bridging layer is 0.025 mm (the thickness of the bridging layer is 10% of the thickness of the base film).

[0075] S310, preparation of zirconium-based organic framework material particles (numbered MIP-202(Zr) MOFs): put 10 mL of deionized water into a blue-capped bottle, add 2.8 g of L-aspartic acid, and stir at room temperature at 400 r / min. 2.33 g zirconium tetrachloride (ZrCl4) was added to a blue-capped bottle in 6 portions. After stirring for 15 min, the mixture was transferred into an oven until the dispersion was uniform and reacted at 120 °C for 2.5 h. After cooling to room temperature, the MIP-202(Zr) MOFs suspension was centrifuged and washed three times with a 50% volume fraction of methanol / water mixture to remove excess reaction substances to obtain purified MIP-202(Zr) MOFs. The purified MIP-202(Zr) MOFs was placed in a drying oven and dried at 60 °C for 12 h to obtain the final product, MIP-202(Zr) MOFs particles, with an average particle size of about 66 nm and an average specific surface area of ​​1330 m2 / g; placing the MIP-202(Zr) MOFs particles in a scanning electron microscope to obtain a scanning electron microscope image, such as Figure 2 Indicate, combine Figure 2 It can be seen that the MIP-202(Zr)MOFs prepared in the present application have uniform particle size and present a multi-faceted crystal configuration, and the surface of the multi-faceted crystal configuration is smooth.

[0076] S320, forming a zirconium-based organic framework material on the surface of the bridging layer away from the ABS-based film: dispersing the MIP-202 (Zr) MOFs particles of step S310 into deionized water to form a suspension, the concentration of which is 12 g / L.

[0077] The surface of one side of the ABS base film containing the bridge layer prepared by S220 was ultrasonically cleaned, and the membrane after ultrasonic cleaning was placed in the above suspension with a concentration of 12g / L and stirred continuously for 24 hours. Then, it was assembled under vacuum assistance, and after the assembly was completed, it was filtered and cleaned with deionized water to obtain a composite membrane material containing a bridge layer.

[0078] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 3A , combined with Figure 3A Particles of zirconium-based organic framework materials can be observed.

[0079] The composite film material containing the bridging layer prepared in this example was placed in an energy dispersive X-ray spectrometer to obtain Figure 3B , combined with Figure 3B It can be seen that the Zr element can be clearly observed in the composite film material, which indicates that the particles of the zirconium-based organic framework material are composited onto one side surface of the bridging layer in the present application.

[0080] Example 1-2 A method for preparing a composite membrane material comprising a bridging layer is provided. The method is different from that in Example 1-1 in that the concentration of the suspension formed by the MIP-202(Zr)MOFs particles in step S320 is 4 g / L, and other aspects are the same as those in Example 1-1.

[0081] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 3C .

[0082] Examples 1-3 A method for preparing a composite membrane material comprising a bridging layer is provided. The method is different from that in Example 1-1 in that the concentration of the suspension formed by the MIP-202(Zr)MOFs particles in step S320 is 8 g / L, and other aspects remain the same as those in Example 1-1.

[0083] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 3D .

[0084] Examples 1-4 A method for preparing a composite membrane material comprising a bridging layer is provided. The method is different from that in Example 1-1 in that the concentration of the suspension formed by the MIP-202(Zr)MOFs particles in step S320 is 16 g / L, and other aspects remain the same as those in Example 1-1.

[0085] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 3E .

[0086] Comparative Example 1 A method for preparing a composite membrane material comprising a bridging layer is provided, the preparation method being different from that of Example 1-1 in that the concentration of the suspension formed by the MIP-202(Zr)MOFs particles in step S320 is 0 g / L, and other aspects are the same as those of Example 1-1, wherein the coating weight per unit area of ​​the zirconium-based organic framework material particles on one side surface of the above-mentioned bridging layer is zero.

[0087] The composite membrane material containing the bridging layer prepared in this example was placed in a scanning electron microscope to obtain a scanning electron microscope spectrum, and the Figure 3F ,Should Figure 3F The surface of the composite membrane material shown is smooth, and no particles are observed.

[0088] Combination FIG. 3C to FIG. 3F It can be seen that the state of particles on the surface of the composite membrane material can be observed by electron microscopy to evaluate the preparation method.

[0089] Comparative Example 2 An ABS base film is provided. The ABS base film is the ABS base film prepared in Example 1-1. No bridging layer is formed on the surface of the ABS base film, and no zirconium-based organic framework material is generated. Other aspects are the same as those in Example 1-1.

[0090] Comparative Example 3 A method for preparing a composite membrane material including a bridging layer is provided. The method is different from that in Example 1-1 in that an iron-based organic framework material is generated on a surface of the bridging layer that is away from the base membrane. The specific preparation process of the iron-based organic framework material includes: Trimellitic acid (H3BTC) and Fe(NO3)3·9H2O in a molar ratio of 0.66:1 were added to deionized water, and then HNO3 was added to adjust the pH value of the reaction system to 4. The molar ratio of HNO3 to Fe(NO3)3·9H2O was 1:4. After sufficient stirring, the mixture was transferred into a 2L reactor and crystallized at 180°C for 12 hours. After the crystallization was completed, the mixed solution was filtered to obtain an orange-yellow crude product.

[0091] The crude product was washed in hot deionized water at 70°C and hot ethanol at 65°C for 3 hours respectively to remove unreacted raw materials, filtered, and the solid sample was collected and dried in an oven at 120°C for 12 hours to obtain an iron-based organic framework material.

[0092] The membrane after ultrasonic cleaning was placed in a suspension of the above iron-based organic framework material with a concentration of 0.8 g / L and stirred continuously for 24 hours.

[0093] Other aspects remain the same as those of Example 1-1.

[0094] Example 2-1 A method for preparing a composite membrane material including a bridging layer is provided. The method is different from Example 1-1 in that, during the preparation of the ABS base membrane, the membrane pore size process parameters are adjusted to print an ABS base membrane with a pore size of 240 μm×400 μm, and the thickness of the ABS base membrane is 312 μm. In addition, the thickness of the bridging layer is 0.012 mm (the thickness of the bridging layer is 4% of the thickness of the base membrane). Other aspects are the same as Example 1-1.

[0095] Example 3-1 A method for preparing a composite film material including a bridging layer is provided. The method is different from Example 1-1 in that the ABS base film is replaced with a polylactic acid base film, and the specific printing process includes drawing a base film pattern by a computer, replacing the substrate with PLA for printing to form a polylactic acid base film, the polylactic acid base film has a pore size of 100 μm×240 μm, a thickness of the polylactic acid base film of 200 μm, and a thickness of the bridging layer of 0.04 mm (the thickness of the bridging layer is 20% of the thickness of the base film). Other aspects are the same as Example 1-1.

[0096] Example 4-1 A method for preparing a composite membrane material comprising a bridging layer is provided. The preparation method is different from that of Example 1-1 in that the polydopamine bridging layer is replaced by a bridging layer of a tannic acid polymer having a weight-average molecular weight of 25100. Other aspects remain the same as those of Example 1-1.

[0097] Example 5-1 A preparation method of a composite membrane material including a bridging layer is provided, and the preparation method is different from Example 1-1 in that: after the ABS base membrane is prepared, the ABS base membrane with a certain aperture is used to prepare a corresponding plasma-modified 3D printed ABS separation membrane according to the following steps: cleaning and drying the base membrane; the prepared ABS base membrane is fully cleaned with pure water, and then dried to remove moisture, and specifically, it can also be placed in an oven at 60°C to dry, to obtain a pre-treated ABS base membrane. Plasma treatment of the base membrane; using plasma surface treatment equipment, specifically Harrick plasma cleaning machine PDC-32G-2, in a vacuum state, the base membrane is plasma treated with air as a reaction gas to form a nanostructure layer on the surface of the base membrane; wherein the radio frequency frequency is 13.56MHz, and the radio frequency power is 18W.

[0098] Other aspects remain the same as those of Example 1-1.

[0099] Test Case (1) Testing the water contact angles of the films obtained in the above embodiments and comparative examples: The measuring instrument is a contact angle meter produced by Kino Corporation of the United States. The specific testing process is to cut each film into small pieces, paste them on a glass slide, and place them on a water contact angle machine for direct measurement.

[0100] The test results of Examples 1-1 to 1-4 and Comparative Example 1 are as follows Figure 4A and Figure 4B The test results of all embodiments and comparative examples are shown in Tables 1 to 3.

[0101] (2) Testing the underwater oil contact angle of the films obtained in the above embodiments and comparative examples: The measuring instrument is a contact angle meter produced by Kino Corporation of the United States. The specific testing process is to cut each membrane into small pieces, paste them on a glass slide and put them into fiberglass. Water is added to the fiberglass and diiodomethane is used as the oil for direct measurement.

[0102] The test results of Examples 1-1 to 1-4 and Comparative Example 1 are as follows Figure 5A and Figure 5B The test results of all embodiments and comparative examples are shown in Tables 1 to 3.

[0103] (3) Testing the water flux and retention rate of the membranes prepared in the above embodiments and comparative examples: The flux was measured by injecting 25 mL of deionized water into the micro-filter cup and recording the time it takes for the water to penetrate through the membrane pores to the bottom of the beaker.

[0104] The retention rate is calculated by weighing and recording the initial weight of the oil (m1) and the initial weight of the device (m2), pouring them into the device, recording the weight of the device and the oil (m3), and recording the ratio of the weight of the device and the oil to the initial weight of the oil and the initial weight of the device, using diiodomethane as the oil liquid.

[0105] The test results of Examples 1-1 to 1-4 and Comparative Example 1 are as follows Figure 6 The test results of all embodiments and comparative examples are shown in Tables 1 to 3.

[0106] (4) Testing the separation effect of the membranes prepared in the above-mentioned Examples 1-1 on oil-water mixtures: The test method is the same as above, and the oils include n-hexane, n-heptane, petroleum ether, gasoline, and soybean oil. The volume ratio between each oil and each water is 1:1.

[0107] The test results of Example 1-1 are as follows Figure 7 The test results of all embodiments and comparative examples are shown in Tables 1 to 3.

[0108] (5) Testing the cyclic stability of the membranes prepared in the above-mentioned Examples 1-1 after treating the oil-water mixture multiple times: A micro filter cup was used for measurement. The flux measurement was performed by injecting 25 mL of deionized water into the micro filter cup, recording the time for water to penetrate through the membrane pores to the bottom of the beaker, weighing the initial weight of the oil (m1) and the initial weight of the device (m2) and recording them, pouring them into the device, recording the weight of the device and the oil (m3), and recording the ratio of the weight of the device and the oil to the initial weight of the oil and the initial weight of the device.

[0109] After briefly flushing the membrane, the above experiment was repeated until the separation efficiency of the membrane changed.

[0110] The test results of Example 1-1 are as follows Figure 8 The test results of all embodiments and comparative examples are shown in Table 1.

[0111] Table 1 Performance list

[0112] Table 2 Performance list

[0113] Table 3 Performance list

[0114] In summary, the design method provided in the present application can ensure the stability of the recycling of the membrane itself while having good oil-water separation efficiency.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A composite membrane material comprising a bridging layer, characterized in that: include: Base film: including any one of acrylonitrile-butadiene-styrene copolymer or polylactic acid; A bridging layer is located on one side of the base film; the bridging layer includes a polymer, and the polymer includes a structural unit derived from a phenol monomer; Zirconium-based organic framework material: located on a surface of the bridging layer facing away from the base film.

2. The composite membrane material according to claim 1, characterized in that: The phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols; and / or; The weight average molecular weight of the polymer is 1000-30000.

3. The composite membrane material according to any one of claims 1 to 2, characterized in that: The zirconium-based organic framework material comprises any one or more of micropores, mesopores or macropores, and at least one of the micropores, mesopores or macropores is interconnected to form a porous structure; and / or; The zirconium-based organic framework material includes particles, and the average particle size Dv50 of the particles is 50nm~300nm; and / or; The zirconium-based organic framework material comprises particles, and the specific surface area of ​​the particles is 1000 m 2 / g~1500m 2 / g.

4. The composite membrane material according to any one of claims 1 to 2, characterized in that: The base film is made by 3D printing method; The base film has a porous structure, and the average pore size of the porous structure is 100 μm to 400 μm; The average pore height of the porous structure is 100 μm to 500 μm.

5. The composite membrane material according to any one of claims 1 to 2, characterized in that: The thickness of the bridging layer is 4% to 20% of the thickness of the base film.

6. A method for preparing the composite membrane material according to claim 1, characterized in that: The preparation process includes the following: Providing a base film: the base film is prepared by a melt deposition method in 3D printing; placing the base film in a solution containing a phenol-derived monomer and shaking the solution to form a bridging layer; A zirconium-based organic framework material is coated on a surface of the bridge layer that is away from the base membrane to form a composite separation membrane material.

7. The preparation method according to claim 6, characterized in that: The shaking treatment is carried out at room temperature, the shaking frequency is controlled to be 20 rpm to 300 rpm, and the shaking treatment time is 10 h to 30 h.

8. The preparation method according to claim 6 or 7, characterized in that: The steps of preparing the zirconium-based organic framework material include: The zirconium-based organic framework material particles are dispersed in deionized water to form a suspension, wherein the concentration of the suspension is greater than zero and less than 20 g / mL.

9. The preparation method according to claim 8, characterized in that: The steps of preparing the zirconium-based organic framework material particles include: Add L-aspartic acid to a reaction container filled with deionized water, stir at room temperature for a period of time, add a zirconium ion precursor in batches, stir evenly to obtain a mixed solution, heat the mixed solution for a period of time, cool to room temperature after the reaction is completed to obtain a suspension, and centrifuge the suspension to obtain the zirconium-based organic framework material.

10. Application of a composite membrane comprising a bridging layer in the field of oil-water separation, characterized in that: The composite membrane is the composite membrane material according to any one of claims 1 to 5 or the composite membrane material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Method for preparing dopamine cross-linked MOFs separation membrane

    CN112691553A

  • Method for preparing oil-water separation membrane containing metal organic framework material

    CN112755799A

  • Difunctional metal-organic framework material modified composite membrane as well as preparation method and application thereof

    CN112871146A

  • Modified separation membrane as well as preparation method and application thereof

    CN115532082A

  • Zirconium-based metal organic framework nano material as well as preparation method and application thereof

    CN116041726A